Common fixed point theorem for generalized nonexpansive mappings on ordered orbitally complete metric spaces and application - NASHINE, Hemant Kumar; AGARWAL, Ravi P. (Studia Universitatis Babeș-Bolyai Mathematica, 2017)
We propose a common fixed point theorem for new notion of generalized nonexpansive mappings for two pairs of maps in an ordered orbitally complete metric space. To illustrate our result, we give throughout the paper two examples. Existence of solutions for certain system of functional equations arising in dynamic programming is also presented as application. Mathematics Subject Classification (2010): 47H10, 54H25.